Improving mood through physical activity for carers and care recipients (IMPACCT): Protocol for a randomised trial - Dow, B.; Moore, K.; Russell, M.; Ames, D.; Cyarto, E.; Haines, T.; Hill, Keith; Lautenschlager, N.; Mackenzie, L.; Williams, S.; Loi, S.; Mackintosh, S. (2013)
Introduction: Family carers play an important role in providing care for frail older Australians. Carers have increased rates of depression, burden and poor physical health compared with non-carers. Physical activity has been shown to improve outcomes; however there is limited research investigating outcomes in older carers and less on physical activity for both the carer and care recipient. Research question: Does a home-based individualised physical activity intervention designed for both the carer and care recipient improve depression severity in older carers? Participants and setting: 273 community-dwelling carers with depressive symptoms and their care recipients will be recruited for a randomised controlled trial. Baseline assessment will consist of functional, psychological, and physical measures and information about service use. Intervention and control: Participants will be randomised to receive either a physical activity program (intervention), a social support program (social control), or usual care (control). The intervention and social control groups will have five home visits over six months. Measurements: All participants will be re-assessed after completion of the program and then six months later to evaluate sustainability of outcomes. The primary outcome measure is the 15-item Geriatric Depression Scale for carers. Secondary outcomes include physical measures for carers and care recipients, carer burden, carer satisfaction, care recipient depression, and cost-effectiveness. All assessors will be blind to group allocation. Discussion: This study has the potential to demonstrate that physical activity interventions can be delivered simultaneously to older carers and care recipients to improve mental and physical outcomes. © 2013 Australian Physiotherapy Association.